MEKANISME PEMILIHAN KEPALA NEGARA DALAM ISLAM DAN HUKUM POSITIF DI INDONESIA - Sutisna (Institut Agama Islam Sahid Bogor, 2020)
The presence of a head of state in the life of the nation and state is a necessity, his presence is expected to be a protector for all citizens. Such is the urgency of a head of state, his presence has become a necessity for all human beings in their various communities. In Islam, the presence of the head of state is expected to be able to carry out the laws of Allah ta'ala and be a protector for all people. Meanwhile, the mechanism for electing the head of state in Indonesia is carried out by means of direct elections by the people to elect candidates for head of state directly. Prior to the direct election model, in Indonesia the head of state was elected by the House of Representatives. The DPR itself is elected by the people by means of a general election mechanism.This study shows that the mechanism model for selecting the head of state is in Islam and in Indonesia, there are some similarities in the election process, namely that the election of the head of state is carried out with the agreement of all citizens. They have the right to choose their head of state in the best possible way. If in Islam the election mechanism is not regulated directly, then in Indonesia it is regulated by Law no. 23 of 2003 concerning the election of president and vice president. The striking difference in this mechanism is that in Islam the election of the head of state is based on Islamic values ​​and must be in harmony with the existing regulations, while the general election in Indonesia is only based on democracy, namely power in the hands of the people.